Optimalisasi Peningkatan Penjualan Menggunakan Media Sosial Tiktok - Mesran, Mesran; Suginam, Suginam; Joli Afriany; Dwika Assrani (Forum Kerjasama Pendidikan Tinggi, 2024)
This research aims to optimize increased sales through the use of TikTok social media. TikTok, as a rising social media platform, offers various features that businesses can use to increase visibility and engagement with potential customers. The main problem faced is how to utilize TikTok's features effectively to increase sales and attract the attention of a wider audience. The solutions in this research include creative content strategies, the use of influencers, and trend analysis to ensure that marketing campaigns reach the right target audience and generate the desired conversions. This research uses a case study method on several small and medium enterprises (SMEs) that have utilized TikTok as part of their marketing strategy. Data was collected through in-depth interviews, surveys and analysis of the performance of TikTok campaigns that have been run by these SMEs. The research results show that the use of creative and interesting short video content can significantly increase user interaction. In addition, collaboration with TikTok influencers has proven effective in increasing product reach and credibility in the eyes of consumers. Other results show that trend analysis and setting the right posting time are very influential in determining the success of a marketing campaign on TikTok. From these results, it can be concluded that TikTok is a platform that has great potential for increasing sales, especially for SMEs who are able to utilize creative features and appropriate marketing strategies. Recommendations from this research include developing authentic and relevant content, as well as using analytics to continuously adapt marketing strategies according to changing trends and consumer behavior. Thus, this research provides practical guidance for businesses to optimize the use of TikTok in efforts to increase sales, as well as offering insight into the importance of adaptation and innovation in digital marketing strategies. This research also emphasizes the importance of consistency in presenting interesting and relevant content. Considering TikTok is a very dynamic platform, businesses need to stay up to date with the latest developments and adapt their strategies quickly. In addition, utilizing features such as TikTok Ads and TikTok Shopping can provide additional encouragement in achieving sales goals. TikTok Ads, for example, allow businesses to target more specific audiences, while TikTok Shopping makes it easy for users to directly purchase products they see in videos. This research shows that TikTok is not just an entertainment platform, but also a powerful marketing tool if used with the right strategy. By harnessing the potential of TikTok, SMEs can expand their market reach and increase sales significantly. It is hoped that this research can be a reference for businesses who want to develop their digital marketing strategy and maximize sales potential through TikTok social media.